1989
DOI: 10.1007/bf01534871
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of prolactin and tumor necrosis factor-beta genes on human chromosome 6p using lymphoblastoid cell deletion mutants

Abstract: A collection of human B lymphoblastoid cell lines (LCLs) was used to map two genetic sequences for which polymorphism had not been identified: human prolactin (PRL) and tumor necrosis factor-beta (TNFB). The LCLs have overlapping deletions on chromosome 6p produced by gamma-irradiation of LCL 721. After using two chromosome 6p sequences for which LCL 721 is heterozygous to validate our scanning densitometry (SD) method for inferring gene copy number, SD was used to map TNFB and PRL. TNFB maps to the interval b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…More interesting is the close genomic linkage between HLA alleles and the prolactin gene. Indeed, human prolactin gene is located on chromosome 6 (Owerbach et al, 1981), more particularly in the interval 6p22.2 to p21.3 (Evans et al, 1989) close to specific HLA alleles. This regional assignment is of interest because a recent study (Brennan et al, 1997) presented data that there may be linkage disequilibrium between HLA-DRB1 alleles and microsatellite marker close to the prolactin gene among women with rheumatoid arthritis and systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…More interesting is the close genomic linkage between HLA alleles and the prolactin gene. Indeed, human prolactin gene is located on chromosome 6 (Owerbach et al, 1981), more particularly in the interval 6p22.2 to p21.3 (Evans et al, 1989) close to specific HLA alleles. This regional assignment is of interest because a recent study (Brennan et al, 1997) presented data that there may be linkage disequilibrium between HLA-DRB1 alleles and microsatellite marker close to the prolactin gene among women with rheumatoid arthritis and systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…The human prolactin gene (PRL) gene, located on chromosome 6p22.3 [2], encodes for a 220 aminoacids, 23 kDa monomeric protein originating from cleavage of the 26 kDa preprolactin molecule, which is mainly produced by the cells of the anterior pituitary and placenta, precisely by those of the decidualized endometrium [3]. The hormone has essential functions in regulating breast development and milk production in women, but also plays pleiotropic functions as osmoregulation, angiogenesis and immunoregulation [4].…”
mentioning
confidence: 99%
“…The human prolactin gene is situated on the short arm of chromosome 6, close to the major histocompatibility complex (MHC) (33). Previous studies have found linkage disequilibrium between MHC genes known to be associated with rheumatoid arthritis and SLE (34), raising the possibility that polymorphisms in the upstream regulatory regions of the human prolactin gene, which perhaps determine levels of lymphocyte-specific transcription, might be associated with disease.…”
mentioning
confidence: 99%